Work Motivation Of Employees At The Rakyat Nusantara Credit Bank Ampera Bhakti Tanjungsari - Rani Munggaran (Universitas Sebelas April, Fakultas Ekonomi dan Bisnis, 2023)
The focus of this research is to see how the Employee Work Motivation at the Bank Pekreditan Rakyat Nusantara Ampera Bhakti Tanjungsari. The purpose of this study is to find out what kind of work motivation is applied to the company, the type of research t hat will be used in the preparation of the thesis is a qualitative method with one variable, namely employee motivation. The techniques that will be used are observation, interviews, documentation and data collection, data reduction, data presentation, and drawing conclusions. This research was conducted by selecting 3 informants who were considered to represent their respective employees, namely Manager, Admin and Marketing. Results of research on employee motivation at Bank Perkreditan Rakyat Nusantara Ampera Bhakti Tanjungsari show that work motivation plays an important role for employees to support their performance when associated with the five dimensions, namely: Physical and Biological Needs, Safety and Security Needs, Social Needs, Needs Rewards and Self- Actualization which will later become the main thing in working for the comfort and continuity of the company. Conclusions and suggestions from research on employee work motivation can certainly have a positive impact on the company, as well as being able to improve employee performance in order to achieve company goals.